Reconstruction of the Paradigm of Other Actions and Police Discretion to Minimize Potential Disparities in Fair Law Enforcement - Rr. Dijan Widijowati; Rynaldo P. Batubara (ENDLESS: INTERNATIONAL JOURNAL OF FUTURE STUDIES, 2022)
This study aims to analyze the reconstruction of other paradigms of action and police discretion in order to minimize potential disparities in law enforcement with justice. This study uses a normative juridical method, to link the relationship between norms and the situation in question. Researchers use a philosophical approach, a conceptual approach, and a sociological approach in the sense that several cases are studied for reference to a legal issue, and a statutory approach. The results of this study require an effort to reconstruct the paradigm through refining the norms regarding Other Actions and Discretion, so that the philosophical, social, and juridical objectives of existence and being given the authority to carry out Other Actions and Discretion are right on target.